Analisis Efisiensi Usahatani Padi Sawah (Studi Kasus di Subak Guama, Kecamatan Marga, Kabupaten Tabanan) - NI MADE AYU CITRA LAKSMI; I KETUT SUAMBA; I G.A.A AMBARAWATI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2012)
ABSTRACT Analysis of Rice Production Efficiency (Case Study in Subak Guama, Marga District, Tabanan Regency) The research was conducted in Subak Guama, District Marga, Tabanan regency from November 2011 to April 2012. Determined the selection of study sites intentionally (purposive sampling) with particular consideration of the Tabanan Regency Guama Subak is a center of rice production in the province of Bali. Efficient use of production factors were analyzed with the equation of the Cobb-Douglas production function, technical efficiency, allocative efficiency and economic efficiency and the magnitude of the benefits of rice farmers were analyzed with analysis of costs and benefits. The analysis showed that the seed production function, urea and NPK fertilizer (Phonska and Rainbow) have real impact on rice farming. Test results and economic allocative efficiency suggests that to get the maximum income of farmers to reduce pesticide use and the benefits of farmers in the rice paddies in one growing season is in March through the month of June 2011 amounting to Rp. 16,102,582.00 per hectare. Therefore, to achieve optimum production and maximum profit it is necessary to the addition of seeds, fertilizers, Urea, NPK fertilizer (Phonska and Rainbow) and reduce the amount of pesticide use that exact type, dose, time and route of administration. Farmers utilizing Koperasi Usaha Agribisnis Terpadu (KUAT) Subak Guama for capital assistance, price certainty, the certainty of marketing and high profit levels so that farmers do not lose money with a middleman. Keywords: efficiency, profit, production factor, rice paddies